Aplicabilidade do TTC para a detecção de bacteriúria - Ramos-Pollis, T. Z. [UNESP]; Pizzolitto, Elisabeth Loshchagin [UNESP]; Raddi, Maria Stella Gonçalves [UNESP]; Pizzolitto, Antonio Carlos [UNESP] (My University, 2008)
Laboratory tests to detect urinary infection at a lawer cost than uroculture are necessary. Triphenyl tetrazolium chloride was evaluated in parallel with uroculture in 342 urine samples, for the detection of significant bacteriuria. The results showed that the test has high sensitivity (91.3%) but low specificity (64.3%), and negative predictive value 99.0%. Although the test cannot replace uroculture as a diagnostic method, it can be recommended for preliminary screening, and could eliminate the need for uroculture of negative samples.

Exames laboratoriais para detecção da infecção urinária com custo menor que da urocultura têm sido buscados. O cloridrato de rifeniltetrazólio foi avaliado em 342 amostras de urina aralelamente à urocultura objetivando a detecção de bacteriúria significativa. Os resultados demonstraram que o teste apresenta boa sensibilidade (91,3%) e baixa especificidade (64,3%), com valor preditivo negativo de 99,0%. Apesar do teste não substituir a urocultura como método diagnóstico, pode ser recomendado para a triagem de bacteriúria, eliminando a realização da cultura em amostras negativas. Palavras-chave: bacteriúria; TTC; infecção do trato urinário.
Applicability of TTC test to bacteriuria detection
Keywords: Bacteriuria; TTC; Urinary tract infection; triphenyltetrazolium; bacterium culture; bacterium detection; diagnostic test; nonhuman; predictive validity; screening; sensitivity and specificity; urinalysis